2015
DOI: 10.1371/journal.pntd.0004316
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Microsatellite Markers Derived from the Whole Genome Analysis of Taenia solium

Abstract: BackgroundInfections with Taenia solium are the most common cause of adult acquired seizures worldwide, and are the leading cause of epilepsy in developing countries. A better understanding of the genetic diversity of T. solium will improve parasite diagnostics and transmission pathways in endemic areas thereby facilitating the design of future control measures and interventions. Microsatellite markers are useful genome features, which enable strain typing and identification in complex pathogen genomes. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…In addition, this finding is consistent with the previous report that mononucleotide SSR repeats are more frequent in eukaryotic genomes than other SSR repeat types (Sharma et al 2007). However, dinucleotide SSR repeats are the most frequent type in dicotyledons (Kumpatla and Mukhopadhyay 2005), Taenia solium (Pajuelo et al 2015), Drosophila (Katti et al 2001), and rodents (Toth 2000), while trinucleotide SSR repeats are the most prevalent type in a number of prokaryotes (Kim et al 2008;Sharma et al 2007) and yeast (Katti et al 2001). The second most frequent SSRs in camelid genomes are dinucleotides, accounting for 25.08-33.94% of all SSRs.…”
Section: Diversity Of Microsatellite Distribution In Camelid Genomessupporting
confidence: 92%
“…In addition, this finding is consistent with the previous report that mononucleotide SSR repeats are more frequent in eukaryotic genomes than other SSR repeat types (Sharma et al 2007). However, dinucleotide SSR repeats are the most frequent type in dicotyledons (Kumpatla and Mukhopadhyay 2005), Taenia solium (Pajuelo et al 2015), Drosophila (Katti et al 2001), and rodents (Toth 2000), while trinucleotide SSR repeats are the most prevalent type in a number of prokaryotes (Kim et al 2008;Sharma et al 2007) and yeast (Katti et al 2001). The second most frequent SSRs in camelid genomes are dinucleotides, accounting for 25.08-33.94% of all SSRs.…”
Section: Diversity Of Microsatellite Distribution In Camelid Genomessupporting
confidence: 92%
“…This is in agreement with the fact that the coding regions have less frequent microsatellites than the non-coding ones 22 . In addition, ITS1 dinucleotide motifs were the most abundant in taeniids as previously shown in other species 35 .…”
Section: Discussionsupporting
confidence: 76%
“…Accordingly, in ITS1 region, a higher GT content was found in the study in agreement with Pajuelo et al . 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Future research using microsatellite DNA markers to link cysts found in pigs to their specific parent tapeworm may help to better understand the spatial and environmental mechanism of T. solium transmission. 33 In conclusion, we demonstrated significant clustering of viable porcine cysticercosis infection in the immediate surroundings of confirmed T. solium tapeworm carriers. This study contributes to a growing body of evidence that T. solium tapeworm carriers represent important sources of infection to pigs raised in their immediate vicinity.…”
Section: Discussionmentioning
confidence: 57%